CODESRIA Bulletin Online, No. 4, February 2022 - The Unresolved Question of Identity in Ethiopia - Zewde, Bahru (CODESRIA Bulletin, 2022)
This article articulates an argument for pan-Ethiopian identity in understanding processes of state formation in Africa. The article is part of CODESRIA’s initiative to welcome intellectual reflections and dialogue around different, even contending, positions on the Ethiopian question and how comparative analyses of similar situations in Africa might shed light on attempts to end the crisis and explore suitable ways forward. CODESRIA Bulletin is a platform for ideas and opinion that contribute to better understanding of society and among many other topics, we aim here to discuss the challenge of nation-building in Africa. The Council welcomes contributions that will advance rigorous intellectual debate on these matter for review and publication as a way of facilitating intellectual dialogue on these issues. Introduction The recent conflict in northern Ethiopia has put the country in the international spotlight. In a pattern rather reminiscent of Darfur in the first decade of this century, Tigray has become a household name and genocide the buzzword. Over a decade ago, Mahmood Mamdani wrote a scathing critique of the ‘Save Darfur’ movement (Mamdani 2010), highlighting the liberal use of the term ‘genocide’. But the world does not seem to have become the wiser for it. ‘Save Darfur’ has been replaced by ‘Stand with Tigray’. The agitprop value of the term genocide is so high that the Tigray People’s Liberation Front (TPLF) and its partisans have been harping on it. This has continued even after the joint investigation of the UN OHCHR and the Ethiopian Human Rights Commission established that, while atrocities were committed by all parties to the conflict, there was no act that justified the use of the genocide label. It has been sustained even after TPLF forces have committed large-scale atrocities, including rape, mass executions and looting and wanton destruction of health and educational facilities, in the wake of their incursions into the Amhara and Afar regions after the unilateral declaration of ceasefire by the federal government in June 2021.[2] A proper understanding of the Ethiopian historical context has been woefully lacking in the media reports and the analyses of ‘pundits’. Aside from the longue durée of Ethiopian history, even the short span of the three decades when the TPLF held central political power has eluded most analyses. And yet those three decades form such an important backdrop to the current conflict. In the longer perspective, the conflict emanated from the as yet unresolved question of identity in Ethiopian politics. Since the middle of the twentieth century, Ethiopian identity, which had been almost axiomatic, has been subjected to a severe test. A counter-narrative has exposed the glaring deficiencies of that identity. The remedy prescribed to address those deficiencies, which gave primacy to ethnic identity, far from resolving the problem, seems to have aggravated it. The current conflict is the latest (and hopefully the last) episode in this tension between pan-Ethiopian and ethnonationalist identity. This article is intended to throw some light on the trajectory of identity politics in Ethiopia. The Evolution of Pan-Ethiopian Identity The Ethiopian state is notable for its antiquity and its resilience. Legendary origins aside, it can be traced back at least two thousand years. Aksum, which has come to assume such negative connotations in the recent conflict, was its foundation. It gave Ethiopia its monarchy, its two major religions (Orthodox Christianity and Islam), its unique Ge’ez syllabary, and its architectural and musical traditions. Just as the country’s medieval rulers (c. 1270–1529) traced their dynastic line back to Aksum and beyond, its modern emperors evoked the might and grandeur of the medieval kings. In a process that combined peaceful overtures with physical violence, Emperor Menilek (r. 1889–1913) forged the modern Ethiopian state. Haile Selassie I, who was crowned in 1930 after a protracted struggle for succession, initiated an unprecedented centralisation of power. Schools and the military were the two pillars of the process of nation-building, even if these were characterised by a high dosage of assimilation. Not only did the Ethiopian state show remarkable continuity, but it was also resilient in the face of both external and internal stresses. It survived the devastating raids of Queen Yodit (Gudit) in the tenth century, the Wars of Ahmad Gragn and the massive population movements of the Oromo in the sixteenth century, the uncertainty that attended the ailment and eventual demise of the mighty Menilek, the tribulations of the 1974 Revolution, and the change of regime in 1991. Its rulers put aside their internal differences and fought as one to defeat Italian colonial intrusion at the Battle of Adwa in 1896. That victory not only guaranteed the country’s independence but also became a beacon of freedom and dignity to Africans in particular, and black people in general. Similarly, Ethiopians rallied against the Fascist Italian Occupation (1936–1941) by waging a guerrilla war that cut the enemy’s tenure short. They rallied yet again from 1977 to 1978 to reverse the Somali invasion, and from 1998 to 2000 during the Ethiopian-Eritrean border war. Until about the middle of the twentieth century, regional affiliation was a more important marker than ethnic identity. This was particularly true of the Amhara, who identified themselves by their regions (Gojjam, Gondar, Shawa, Wollo) or even sub-regions (Damot, Gayent, Manz, Yefat, Bulga, Yajju, etc.) rather than as Amhara. Indeed, Shawa was the ethnic melting pot par excellence, blending the Amhara, Oromo and Gurage into a distinct geographical entity.[3] Among the Oromo as well, clan identity (Borana, Karayu, Leqa, Salale, Sibu, etc.) was more pronounced than pan-Oromo identity. Even in Tigray, where ethnos and region were relatively more coterminous, sub-regional identity (Adwa, Agame, Enderta, Shire, Tembien) was equally powerful. The fluidity of ethnic identity was reflected in the high degree of interethnic interaction that prevailed, including interethnic marriages. The most ancient people of Ethiopia, the Agaw, became so fused with the Amhara that, except for a few pockets, they practically lost their identity. But the supreme example of interethnic mixing was provided by the Oromo, who experienced a process of reciprocal assimilation with the peoples they came across—assimilating as well as being assimilated (Yates 2020). Wallo is the supreme example of the acculturation of the Amhara and the Oromo. Farther to the west, in Gojjam, the Oromo not only intermingled with the Amhara population but also came to have a decisive role in the power politics of the centre. The boundary between the Amhara and Oromo is quite blurred in the district of Salale. Likewise, there was a great deal of acculturation between the northern Gurage (known variously as Soddo, Kestane or Aymallal) and the adjacent Oromo (Zewde 2008). Interethnic marriages, particularly among the elite, have been common since the wedding of the Hadiya princess, Ite Jan Zela (more famously known as Queen Eleni), to Emperor Ba’eda Maryam (r. 1433–68). This became the norm in the nineteenth and twentieth centuries as interdynastic marriages were arranged to fend off opposition or ensure succession. Thus Emperor Takla Giyorgis of Wag (r. 1868–1971), successor of Emperor Tewodros, was married to the sister of Kassa Mercha of Tigray (the future Emperor Yohannes, r. 1872–1889). The latter’s son was married to the daughter of King Menilek of Shawa. Such arranged interethnic marriages were elevated to the level of an art by Menilek’s spouse, Taytu, who created a web of matrimonial relations to consolidate her power in her husband’s waning years. Likewise, Emperor Haile Selassie’s family was linked by marriage to the ruling houses of Wollo, Tigray, and Wallaga (see, for example, Serekeberhan 2002). Ultimately, these intermarriages helped create a ruling class that had its members coming from different regions of the country. Oromo leaders came to play an important role in the power politics of the Gonderine period, culminating in the establishment of a power bloc that came to be known as the Yajju dynasty. Menelik’s campaigns of territorial expansion in the last quarter of the nineteenth century were spearheaded by his Oromo general, Ras Gobana Dachi. Fitawrari Habte Giyorgis Dinagde, of Oromo-Gurage parentage, emerged as a formidable power-broker during the interregnum between Menelik’s incapacitation and Haile Selassie’s ascent to the throne (Zewde 2008). A cursory survey of Ethiopia’s national icons demonstrates their varied ethnic backgrounds. These include the already cited Habte Giyorgis (Oromo-Gurage), the legendary marathon runner Abebe Bikila (Oromo), the ‘King of Pop’ Tilahun Gessesse (Amhara-Oromo), Ethiopia’s most accomplished poet laureate, Tsegaye Gebre-Medhin (Amhara-Oromo), Emperor Tewodros (Amhara), Emperor Yohannes, the redoubtable general Ras Alula, and the most incisive intellectual of the early twentieth century, Gabra Heywat Baykadagn (all Tigrayans), and Emperors Menilek and Haile Selassie (of mixed Amhara and Oromo parentage). Also of interest is how ethnic culinary specialities attained national status. These include the Amhara (particularly Gondaré) doro wat (chicken curry), the Gurage kitfo, the Oromo chachabsa and the Tigrayan/Eritrean (h)ambasha. The Ascendancy of the Counter-Narrative The above trajectory of pan-Ethiopian identity came under serious challenge in the second half of the twentieth century. The icons became villains. Menilek, the victor of Adwa and the creator of modern Ethiopia, became the ruthless conqueror. His Oromo general, Ras Gobana, became the arch collaborator and traitor. In 1943, an anti-government protest in Tigray known as Wayane severely tested the authority of the newly restored government of Haile Selassie, following the end of Fascist Italian Occupation (1936–1941). While a number of factors contributed to its outbreak, the marginalisation that the province experienced after the death of Emperor Yohannes was a contributory factor. But it was largely confined to the southeastern part of the province and was quickly suppressed (Tareke 1991).[4] Elsewhere, it was not so much marginalisation as downright oppression and exploitation that triggered ethnonationalist movements. In many parts of southern Ethiopia, the territorial campaigns of Menilek were followed not only by the imposition of administrative control but also the appropriation of economic resources (particularly land) and the exercise of various forms of cultural oppression. Although the Oromo on the whole fared relatively better than many of the other southern peoples, some of whom were subjected to enslavement, it was they who felt the first stirrings of ethnonationalism. A self-help association named after the two major branches of the Oromo, Mecha and Tulama, was formed in 1963. The government was uncomfortable with this development and became alarmed when the leaders of the association organised a hasty and ill-considered attempt to assassinate the emperor. The leaders were detained, one of them was subsequently hanged and the association was banned, only to resurface as the Oromo Liberation Front (OLF) in 1974 (Hassen 1998). Simultaneously, for the better part of the 1960s, a peasant rebellion in the Oromo and Somali-inhabited province of Bale posed a serious challenge to central government authority. A much more serious challenge to the pan-Ethiopian thesis emerged in Eritrea. Following the liberation of that country from Italian colonial rule in 1941, Eritreans were divided into those who favoured union with Ethiopia and those who opted for independence. As a sort of compromise, the UN resolved in 1950 to federate Eritrea with Ethiopia. Following the abrogation of the federal arrangement in 1962, a liberation movement emerged in Eritrea, first campaigning for the restoration of the federation but eventually fighting for independence. To give their movement international legitimacy, the Eritrean liberation fronts couched their struggle as an anticolonial one. The OLF took the cue and eagerly adopted the same rhetoric. It was to accommodate these ethnonationalist and regional challenges that the Ethiopian Student Movement (ESM) began to tackle seriously what it called the question of nationalities. The upshot of the two-year debate was the adoption in the summer of 1971 of the Leninist-Stalinist principle of self-determination, up to and including secession. This became the credo not only of the ESM but also the leftist parties that sprouted from it, notably the Ethiopian People’s Revolutionary Party (EPRP) and the All-Ethiopia Socialist Movement (more commonly known by its Amharic acronym, Me’ison). The TPLF, which emerged on the fringes of that movement, also embraced self-determination wholeheartedly as it found it an effective weapon to mobilise the Tigrayan population for the armed struggle that it launched in 1975. The eclipse of the pan-Ethiopian organisations (notably EPRP and Me’ison) through their mutual destruction and the notorious ‘Red Terror’ paved the way for the ascendancy of ethnonationalist organisations like the TPLF and OLF (‘Quest’) (see Zewde 2014, 20018, especially Chapter 6).[5] The victory of the TPLF-spearheaded EPRDF (Ethiopian Peoples’ Revolutionary Democratic Front) over the Darg in 1991 paved the way for the legal consolidation of self-determination, which was first enunciated in the ESM—initially via the Charter of the Transitional Government and next in the 1995 Constitution that established the Federal Democratic Republic of Ethiopia. Ethiopia was divided into nine ethnolinguistic regions. Precedence was given to the ‘nations, nationalities and peoples’ of Ethiopia over the pan-Ethiopian entity. Sovereign power resided in the former rather than the latter. Most importantly, the first sub-article of Article 39 gave the entities an ‘unconditional right to self-determination, including the right to secession’ (Republic of Ethiopia 1995). The principle of self-determination, although meant to address the long-standing problem of the oppression and marginalisation of many nationalities, was faulty in conception and devious in execution. To begin with, it was based on a blind imitation of the Leninist classics rather than a careful reading of Ethiopian history or ethnography. As a result, it accentuated the differences of the various ethnic groups and totally ignored the similarities and interrelationships that have been outlined above. This deficiency was reflected in the fact that the right to secession was prioritised over the advantages of living together, provided that the linguistic and cultural rights of the nationalities were respected. This ‘fixation on secession’ (to borrow a phrase from one of the student leaders of the time) was blissfully explained away as being the surest way of actually discouraging secession. Moreover, it was deemed imperative to bring the Eritrean liberation movement into the common struggle against imperial rule. Secondly, no effort was made to disaggregate the collective appellation ‘nations, nationalities and peoples’, although it was meant to denote a descending order of social organisation. In fact, the fifth sub-article of the same controversial Article 39 gives a blanket definition for all three categories. Thirdly, in view of the fact that some eighty ‘nations, nationalities and peoples’ are known to exist in Ethiopia, it is difficult to see where this splintering of the country into regional states will end. As it turned out, the period since the promulgation of the Constitution has been characterised by various demands for autonomous status, either as a region or zone or a ‘special zone’. Currently, with the breakaway of two new regions from the rather amorphous Southern Nations, Nationalities and Peoples Region (quite a mouthful by itself!), the number of regions in the country has been raised from nine to eleven. Fourthly, although it was stipulated in the Constitution that self-determination was to be exercised by means of a referendum, it was not always clear whether that referendum reflected the actual feeling of the people concerned or was the result of the manipulation of the many ‘liberation fronts’ that have mushroomed in the country. Self-determination comes not only with political autonomy but also with perks and privileges for the governing elite.[6] Equally sobering has been the practical implementation of self-determination. Although the regions were theoretically deemed to be autonomous, they were actually controlled from the centre through the powerful EPRDF party apparatus. Behind every regional president was a TPLF functionary who exercised real power and ensured the party line was adhered to. The TPLF had such hegemonic control over the EPRDF that it became common to pair the two organisations as TPLF/EPRDF. The three other members of the coalition—the Amhara National Democratic Movement (ANDM), the Oromo People’s Democratic Organisation (OPDO) and the Southern Ethiopia Peoples Democratic Front (SEPDF)—had a manifestly secondary status. Even more marginalised were the so-called ‘allied parties’, mostly representing the nationalities on the periphery (Markakis 2011; Aalen 2001). Further, an arrangement that was meant to bring about a harmonious relationship among the different nationalities actually ushered in an era of unprecedented ethnic conflict. Somalis were pitted against Oromo, Gujji against Gedeo and Oromo against Amhara. These conflicts escalated after the TPLF lost its hegemonic position and retreated to its Tigray stronghold, with most of the conflicts being attributed to its strategy to destabilise the Abiy Ahmed government. The relative weakness of that government to enforce its authority, partly emanating from the general spirit of liberalisation that was its birthmark, has accentuated the problem. As a result, hundreds of Ethiopians have lost their lives and hundreds of thousands have been internally displaced. Amhara settlers have suffered the most as they have been targeted by the Oromo Liberation Army (OLA), the armed wing of OLF, in Wallaga and northern Shawa, and armed Gumuz fighters in Beni Shangul. Dénouement? The war that erupted in Tigray in November 2020 is in a way the culmination of this unresolved problem of identity. The much-vaunted harmonious coexistence of nationalities has evaporated into thin air amidst the deafening roar of guns and mutual recriminations of genocide and ethnic cleansing. Tigray, the bedrock of Ethiopian statehood and civilisation, seems poised to break away from Ethiopia. There is nothing more disheartening for an Ethiopian than to see Tigrayans trampling the Ethiopian flag and expressing pride in being privileged to witness (somewhat prematurely, one should add) the breakup of Ethiopia. That is the same flag around which the Tigrayan Emperor Yohannes IV rallied Ethiopians against Egyptian invasion, Italian encroachment, and Sudanese Mahdist incursions. Conversely, the war has reinforced the nascent Amhara nationalism and reinvigorated the residual pan-Ethiopian nationalism. If there were two protagonists of the imperial order, it was the Amhara and the Tigrayans. Now, they have become mortal enemies. Already, as a result of the harassment that the Amhara have suffered in many parts of the country and the inability of the Amhara contingent of the ruling party to come to their defence, a strident Amhara nationalist party known as the National Movement of Amhara (NAMA) has emerged (Tazebew 2021). The war, and in particular the TPLF depredations in the Amhara region, has strengthened Amhara nationalism. Even more significantly, the threat posed by the TPLF has reinvigorated the residual pan-Ethiopian nationalism. Ethiopians of almost all nationalities have rallied behind the federal government in a manner that is reminiscent of Adwa in 1896, the anti-Fascist resistance of 1936–41, the Somali invasion of 1977–78 and the Ethio-Eritrean War of 1998–2000. What is of particular interest is that this pan-Ethiopian patriotism is as strident (if not more) among historically marginalised nationalities, such as the Afar, the Gambellans and the southern peoples. Yet, there are genuine apprehensions that the resolution of the Tigray conflict might not be the end of the story. The position of the Oromo elite has been somewhat perplexing. Its strategy in the past decades has ranged from the creation of an independent Oromia, articulated by the OLF, to achieving self-determination within Ethiopia, as encapsulated by the OPDO (now rechristened Oromo Prosperity). Yet, the boundary between the two has not always been watertight. The impunity with which the OLA has been killing and maiming in the past three years has led to speculation that it might be enjoying the connivance or benevolent neutrality of the ruling Oromo elite. The total destruction of the town of Ataye, only some 200km from Addis Ababa, in April 2021 lent credence to these suspicions. If the Oromo elite is not going to learn from the disastrous outcome of the TPLF’s hegemonic aspirations, Ethiopia will be heading for yet another round of conflict. Hopefully, the much-anticipated national dialogue that is now being launched will address all these outstanding issues and come up with a set of recommendations that could move the country forward. That the 1995 Constitution has to be revised goes without saying. For far too long, it has been venerated like the tablets of Moses or the Holy Bible. That Ethiopia should have some form of federal arrangement has become an inescapable reality. Likewise, ethnic identity is not something to be wished away. Perhaps the solution is an arrangement that recognises ethnic identities but gives pride of place to a pan-Ethiopian identity. The student movement that cast such a spell on Ethiopian politics focused more on social justice (‘Land to the Tiller’) and equality (‘self-determination’) and less on freedom. The recent history of the country has shown that the accent should be placed on political pluralism rather than on self-determination. Notes [1] The ideas in this piece were first presented at a public lecture I delivered at the Stellenbosch Institute for Advanced Study in October 2021 as part of the Fellows’ seminar series. I am grateful to STIAS for granting me the fellowship to help me develop my research on the issue of identity in Ethiopia. [2] See the following for TPLF’s ‘love affair’ with genocide: https://ethiopost.medium.com/tplf-and-genocide-a-love-affair-2e2d8c023e72 and https://www.the-star.co.ke/opinion/star-blogs/2022-01-12-wosen-melaku-tplfs-obsession-with-genocide-and-how-to-end-it/. There is now ample documentation on TPLF atrocities in the Amhara and Afar regions. See, among others, the following links: TPLF War Crimes- Rape- Massacres-90% of Public Infrastructures Ransacked and Deliberately Destroyed; www.theguardian.com/world/2021/sep/09/rebel-forces-accused-of-killing-civilians-north-ethiopia; https://www.reuters.com/investigates/special-report/ethiopia-conflict-tplf/; https://youtu.be/7EckON-2PyQ. [3] See Berhanu Abegaz (https://issuu.com/amharacouncil/docs/the_enigmatic_amara), who defines the Amhara as ‘arguably the most detribalized of Ethiopia’s cultural groups’, and Gerry Salole, 1979, Who are the Shoans?’ Horn of Africa Vol. 2, No. 3, for the unique historical status of Shawa. [4] This is the standard work on the Wayane. [5] See Chapter 6 for ESM’s handling of what it called the ‘national question’ or the ‘question of nationalities. [6] I have discussed the troubled legacy of ESM’s handling of the question in an Amharic piece, ‘The Legacy of the Ethiopian Student Movement on the Question of Nationalities’, which recently got wide publicity online (cf. https://sebategna.com). References Aalen, L., 2001, Ethnic Federalism in a dominant party state: The Ethiopian experience 1991–2000, Chr. Michelsen Institute (CMI) Report R 2002:2, University of Bergen. Hassen, M., 1998, The Macha-Tulama Association 1963-1967 and the Development of Oromo Nationalism, in Jalata, A., ed., Oromo Nationalism and the Ethiopian Discourse: The Search for Freedom and Democracy, Lawrenceville, NJ: Red Sea Press Mamdani, M., 2010, Saviors and Survivors: Darfur, Politics and the War on Terror, Dakar: CODESRIA. Markakis, J. 2011, Ethiopia: The Last Two Frontiers, Oxford: James Currey. Republic of Ethiopia, 1995, The Constitution of the Federal Democratic Republic of Ethiopia, 21 August 1995. Serekeberhan, H., 2002, Building Bridges, Drying Bad Blood: Elite Marriages, Politics and Ethnicity in 19th and 20th Century Imperial Ethiopia, PhD dissertation, Michigan State University. Tareke, G., 1991, Ethiopia: Power and Protest. Peasant revolts in the twentieth century, Cambridge: Cambridge University Press. Tazebew, T., 2021, Amhara Nationalism: The empire strikes back, African Affairs, Vol. 120, Issue 479. Yates, B. J., 2020, The Other Abyssinians: The Northern Oromo and the Creation of Modern Ethiopia, 1855–1913, Rochester: University of Rochester Press. Zewde, B., 2008, The Aymallal Gurage in the Nineteenth Century, in Zewde, B., ed., Society State and History: Selected Essays, Addis Ababa: Addis Ababa University Press. Zewde, B., 2008 EC, Habte Abba Mela: From War Captive to National Leader (in Amharic), 2nd edition, Addis Ababa: Eclipse. Zewde, B., 2014 (2008), The Quest for Socialist Utopia: The Ethiopian Student Movement c. 1960–1974, Oxford: James Currey